Pemakzulan Presiden di Korea Selatan - Frida Aprillia Wahjudi; Nur Rohim Yunus (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
Abstract:Impeachment can occur in every country, even it must be accommodated in the state administration system in a country based on a democratic system, including in this case the State of South Korea. The implementation of dismissal from the highest executive power is due to violations of the provisions of the applicable laws and regulations. This research method uses a normative juridical legal research approach, while the type of research used is descriptive qualitative analytical, and data collection techniques are library research. From this research it is known that the country of South Korea also provides opportunities in the country's constitution to impeach a president who is considered to have violated the laws and regulations. Although the implementation mechanism is slightly different from the mechanism of impeachment in Indonesia.Keywords: Impeachment, President, South Korea